2016
DOI: 10.1002/lt.24515
|View full text |Cite
|
Sign up to set email alerts
|

End‐ischemic reconditioning of liver allografts: Controlling the rewarming

Abstract: Different nonhypothermic preservation modalities have shown beneficial effects in liver transplantation models. This study compares controlled oxygenated rewarming (COR) to normothermic machine perfusion (NMP) to resuscitate liver grafts following cold storage (CS). Porcine livers were preserved for 18 hours by CS. Before reperfusion, the grafts were put on a machine perfusion device (Liver Assist) for 3 hours and were randomly assigned to COR (n = 6) or NMP (n = 5) and compared to standard CS. COR was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Further experiments have indicated that rewarming of the organ during oxygenated machine perfusion could further contribute to improved organ integrity and in vivo functionality through an adapted increase in metabolic activity of mitochondria and tissue cells . Controlled oxygenated rewarming (COR) to 20°C was already shown to have protective capacities and improves organ recovery upon reperfusion …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experiments have indicated that rewarming of the organ during oxygenated machine perfusion could further contribute to improved organ integrity and in vivo functionality through an adapted increase in metabolic activity of mitochondria and tissue cells . Controlled oxygenated rewarming (COR) to 20°C was already shown to have protective capacities and improves organ recovery upon reperfusion …”
Section: Introductionmentioning
confidence: 99%
“…9 Further experiments have indicated that rewarming of the organ during oxygenated machine perfusion could further contribute to improved organ integrity and in vivo functionality through an adapted increase in metabolic activity of mitochondria and tissue cells. 10 Controlled oxygenated rewarming (COR) to 20°C was already shown to have protective capacities and improves organ recovery upon reperfusion. 11 So far, extracorporeal temperature rise during COR had been limited to 20°C, as perfusion solutions had been used that were specifically designed for organ protection at hypothermia and might become inappropriate perfusates at increasing temperatures.…”
mentioning
confidence: 99%
“…These unexpected results compared to the UK trial was speculated to be related to the higher proportion of DCD livers (44% Edmonton trial versus 20% for UK or Toronto trials) or the prolonged cold ischemia time (median, 2 hours 47 minutes) due to uncommonly complex back‐table reconstructions, and HTK donor flush in the Edmonton trial. Additionally, the superiority of COR and SNMP in porcine livers sparked the first successful application or COR in clinical liver transplantation . Rewarming therapies, the newest methodology in machine preservation, may become the ultimate compromise with their ability to capture advantages of relative convenience as compared with NMP, longevity of storage comparable to HMP or SCS, optimal resuscitation in predictive animal models, and predictive ex vivo assessment prior to transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Others found that gradual increase of perfusate flow and oxygen throughout the rewarming period minimized AST/ALT production . Controlled oxygenated rewarming (COR) perfusion was also shown to be superior in recovering energy stores and minimizing hepatocellular and mitochondrial stores after 18 hours of CS as compared with NMP …”
Section: Normothermic Machine Perfusion Settingsmentioning
confidence: 99%
“…Recent experiments are suggesting that the protective effect of hypothermic machine perfusion can be further enhanced by a controlled oxygenated rewarming (COR) and, after preceding cold preservation, the controlled rewarming resulted in significantly better organ recovery than abrupt perfusion with warm perfusate .…”
Section: Introductionmentioning
confidence: 99%